Sistem Pengukuran Keterampilan Pengguna Pada Simulator Las Berbasis Augmented Reality - Chairu Ummam, Mochammad; Noor Prawita, Fathah (eProceedings of Applied Science, 2023)
Abstract— In the industrial world, it certainly cannot be separated from what is called a welding process. The welding process is not cheap because the materials used are very expensive. In addition, welding skills needed to be mastered in a lot of time and materials for so that welders weld objects perfectly. In our final project titled "LAsR: Application of user skills measurement system on an augmented reality-based welding simulator" is designed with the aim of helping teachers and students in conducting practicals and exams during welding with augmented reality (AR) technology. When practicum using the LAsR application, students will be safe when welding is in progress and minimize errors that can occur and teachers can easily assess students who are doing welding exams. With the LAsR application, schools can also save costs when doing welding practicums. With the LAsR application, schools can also save costs when doing practicum. The results of testing in this final project to 40 target users related to the effectiveness, usability, and satisfaction of the application display resulted in an average.Keywords— welding, measurement system, augmented reality, skill